Perbandingan Amalan Dhikr Ism al-DhAt Menurut al-Qushayri dan al-Ghazali - Syed Hadzrullathfi, Syed Omar; Engku Ibrahim, Engku Wok Zin; Rohaizan, Baru (2010)
Practise dhikr ism al-dhat according to al-Qushayri and al-Ghazali, the foremost Sufi's figures known in Sufism, is not many discussed even by eastern and western scholars and Sufi's supporters. Thus, the issue is mainly attempted to be highlighted on this article by analyzing their points of views on the subject as well as the article also tries to make a comparison between the two figures in order to show if there any differences or similarities may occur in the practise. Keywords: Dhikr; Ism al-Dhat; al-Qushayri; al-Ghazall; Sufism